Evaluation of the suitability of Fe40Co30Ni30 as a precursor for Fe-rich FeCoNi-based high-entropy semi-hard magnets. (April 2020) - Jayaraman, T.V.; Rathi, A.; Thotakura, G.V.
Abstract: We evaluated the suitability of Fe40 Co30 Ni30 as a precursor for Fe-rich FeCoNi-based high-entropy semi-hard magnets. Mechanically alloying the metal powders 40 at.% Fe, 30 at.% Co, and 30 at.% Ni for 12 h effected micron-size Fe40 Co30 Ni30 powder comprised of nanocrystalline γ phase. Fe40 Co30 Ni30 evinced semi-hard magnetic properties at room-temperature—saturation magnetization ( M S ) 146 Am 2 /kg and intrinsic coercivity ( H CI ) 4.30 kA/m—as well as at below-room-temperatures. The M S at 0 K, μ H, and H CI at 0 K were estimated as 155 Am 2 /kg, 1.60 μ B, and 7 kA/m, respectively. Alloy powders after thermal-treatment exhibited tunable semi-hard magnetic behavior at below-room temperatures and room temperature; their magnetic properties were comparable to certain commercial semi-hard magnets. The weighted Euclidean distance-based approach of decision-making proposed the Fe-rich FeCoNi medium-entropy alloy—Fe40 Co30 Ni30 —as a favorable precursor, having an optimal combination of properties, for designing and fabricating novel FeCoNi-based high-entropy semi-hard magnets. Highlights: Successfully fabricated Fe40 Co30 Ni30 . Alloy powders were micron-sized constituting nanocrystalline γ phase. As-fabricated and thermally-treated alloys exhibited semi-hard magnetic behavior. Adopted Weighted Euclidean distance-approach to rank Fe-rich FeCoNi precursors. Fe40 Co30 Ni30 is a favorable precursor for fabricating high-entropy semi-hard magnets.